2007
DOI: 10.1093/toxsci/kfm042
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A: 13-Week Oral Toxicity and Cell Proliferation in Male F344/N Rats

Abstract: Ochratoxin A (OTA) is nephrotoxic and a potent renal carcinogen. Male rats are most susceptible to OTA toxicity, and chronic administration of OTA (70 and 210 microg/kg bw) for 2 years has been shown to induce high incidences of adenomas and carcinomas arising from the straight segment of the proximal tubule epithelium. In contrast, treatment with a lower dose of 21 microg/kg bw did not result in increased tumor rates, suggesting a nonlinear dose response for renal tumor formation by OTA. Since the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 34 publications
8
62
1
Order By: Relevance
“…S2). These results are consistent with a previous toxicity study of orally administering OTA for 13 weeks 5 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…S2). These results are consistent with a previous toxicity study of orally administering OTA for 13 weeks 5 .…”
Section: Resultssupporting
confidence: 93%
“…In addition, the differences of the serum biochemical indexes at 13 weeks were higher in high-dose (compared to control) livers than medium-dose (compared to control) livers. Medial-dose OTA does not have impact on the serum chemical or histopathological indexes, which is consistent with OTA studies [4][5][6] . Nonetheless, the derivatives found in the liver indicates that OTA must be metabolized in order to act as a carcinogen 26 .…”
Section: Discussionsupporting
confidence: 88%
“…Comparable findings were described in F344 rats treated with the same dose regimen, 28,29,40 thus confirming comparable sensitivity of Eker rats to OTA nephrotoxicity.…”
Section: Nephrotoxicity and Accompanying Cell Proliferation Is Criticsupporting
confidence: 71%
“…The main difference between Zepnik et al (2003) and the aforementioned studies is that an acidification step was not used in the extraction method (see "Analytical techniques for ochratoxin A toxicokinetic studies" section). However, when the same analytical method was applied in samples from repeated dose studies (Mally et al, 2005;Rached et al, 2007), similar levels of OTA were found between both organs. The authors explained the similar concentration between both organs at higher doses as being due to an effect of redistribution and deposition of OTA in all lipid-rich organs.…”
Section: Distributionmentioning
confidence: 77%